Average Error: 0.0 → 0.0
Time: 20.4s
Precision: 64
$\left(\left(x - \frac{1}{2} \cdot {x}^{2}\right) - \frac{1}{3} \cdot {x}^{3}\right) - \frac{1}{4} \cdot {x}^{4}$
$x - \left(1 \cdot \left(\frac{{x}^{3}}{3} + \frac{{x}^{2}}{2}\right) + {x}^{4} \cdot \frac{1}{4}\right)$
\left(\left(x - \frac{1}{2} \cdot {x}^{2}\right) - \frac{1}{3} \cdot {x}^{3}\right) - \frac{1}{4} \cdot {x}^{4}
x - \left(1 \cdot \left(\frac{{x}^{3}}{3} + \frac{{x}^{2}}{2}\right) + {x}^{4} \cdot \frac{1}{4}\right)
double f(double x) {
double r733582 = x;
double r733583 = 1.0;
double r733584 = 2.0;
double r733585 = r733583 / r733584;
double r733586 = pow(r733582, r733584);
double r733587 = r733585 * r733586;
double r733588 = r733582 - r733587;
double r733589 = 3.0;
double r733590 = r733583 / r733589;
double r733591 = pow(r733582, r733589);
double r733592 = r733590 * r733591;
double r733593 = r733588 - r733592;
double r733594 = 4.0;
double r733595 = r733583 / r733594;
double r733596 = pow(r733582, r733594);
double r733597 = r733595 * r733596;
double r733598 = r733593 - r733597;
return r733598;
}


double f(double x) {
double r733599 = x;
double r733600 = 1.0;
double r733601 = 3.0;
double r733602 = pow(r733599, r733601);
double r733603 = r733602 / r733601;
double r733604 = 2.0;
double r733605 = pow(r733599, r733604);
double r733606 = r733605 / r733604;
double r733607 = r733603 + r733606;
double r733608 = r733600 * r733607;
double r733609 = 4.0;
double r733610 = pow(r733599, r733609);
double r733611 = r733600 / r733609;
double r733612 = r733610 * r733611;
double r733613 = r733608 + r733612;
double r733614 = r733599 - r733613;
return r733614;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(\left(x - \frac{1}{2} \cdot {x}^{2}\right) - \frac{1}{3} \cdot {x}^{3}\right) - \frac{1}{4} \cdot {x}^{4}$
2. Simplified0.0

$\leadsto \color{blue}{x - \left(1 \cdot \left(\frac{{x}^{3}}{3} + \frac{{x}^{2}}{2}\right) + {x}^{4} \cdot \frac{1}{4}\right)}$
3. Final simplification0.0

$\leadsto x - \left(1 \cdot \left(\frac{{x}^{3}}{3} + \frac{{x}^{2}}{2}\right) + {x}^{4} \cdot \frac{1}{4}\right)$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "x - (1/2)pow(x,2) - (1/3)pow(x,3) - (1/4)pow(x,4)"
:precision binary64
(- (- (- x (* (/ 1 2) (pow x 2))) (* (/ 1 3) (pow x 3))) (* (/ 1 4) (pow x 4))))